New skills for new designers: Fashion and textiles - Montagna, G.; Delgado, M. J.; Almeida, I.; Santos, L. (Human Factors for Apparel and Textile Engineering (AHFE 2022), 2022)
This paper is the first part of a research work on new skills for designers and creative industries stakeholders, which aims to identify, organize and promote an updated professional mindset among FAUL students. Through the literature review and the implementation of specific questionnaires to the fashion students, teachers and practitioners, it was intended to draw a current view of the skill set needed to work in fashion design. This questionnaire was adapted from the one used in the O*NET Data Collection Program, considering the particular needs and representing the particular domain of education and training we are studying. The results of this study will serve as the structural basis for the design of new curricula that better respond to the needs of graduate students of the Fashion Design Course at the Faculty of Architecture of Lisbon - University of Lisbon, when they enter the job market.